(untitled) (Palíndromo, 2013)
If we can transform, so too plastic-social space that landscape painters of the century. XIX pledged as images of another world, then we can make this world of landscape painters in something you can experience. Not as a passable living space to escape from the urban centers, but to get a true work of art overall.